2022
DOI: 10.3390/cancers14092078
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Circulating Free DNA Enables Monitoring of Tumor Dynamics in Synovial Sarcomas

Abstract: Background: Synovial sarcoma (SS) is a malignant soft tissue tumor of mesenchymal origin that frequently occurs in young adults. Translocation of the SYT gene on chromosome 18 to the SSX genes on chromosome X leads to the formation of oncogenic fusion genes, which lead to initiation and proliferation of tumor cells. The detection and quantification of circulating tumor DNA (ctDNA) can serve as a non-invasive method for diagnostics of local or distant tumor recurrence, which could improve survival rates due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Less invasive diagnostic techniques such as fluorodeoxyglucose positron emission tomography and circulating tumor DNA are particularly appealing and are actively being evaluated in this setting. 14,15 Within the statistical limitations of our analysis, however, pathologic response cannot be considered a surrogate marker of response and predictor of outcome in pediatric and adult patients with extremity and trunk soft tissue sarcoma treated with neoadjuvant chemoradiotherapy and pazopanib.…”
Section: Discussionmentioning
confidence: 99%
“…Less invasive diagnostic techniques such as fluorodeoxyglucose positron emission tomography and circulating tumor DNA are particularly appealing and are actively being evaluated in this setting. 14,15 Within the statistical limitations of our analysis, however, pathologic response cannot be considered a surrogate marker of response and predictor of outcome in pediatric and adult patients with extremity and trunk soft tissue sarcoma treated with neoadjuvant chemoradiotherapy and pazopanib.…”
Section: Discussionmentioning
confidence: 99%
“…56 Such opportunities exist across a spectrum of disciplines including pathology (eg, pathologic response), imaging (positron emission tomography, T2 magnetic resonance imaging), and biology (eg, methylation, proteomics, circulating tumor DNA). [57][58][59][60][61][62] Currently, these efforts have largely analyzed pediatric and adult patients separately, preventing an opportunity to determine their prognostic significance across the AYA population.…”
Section: Biologymentioning
confidence: 99%
“…Subtype-specific panel sequencing for myxoid liposarcomas and synovial sarcomas [33,34]. DNA from tumor tissue (native or FFPE) and matched controls from whole blood samples are prepared for sequencing by generating libraries using NEB kit NEBNext Ultra II FS DNA Library Prep Kit for Illumina, (New England Biolabs, Ipswich, USA).…”
Section: Dna Isolationmentioning
confidence: 99%
“…Quantification of ctDNA in the peripheral circulation might even surpass common imaging modalities in its sensitivity and specificity to detect tumors or metastases [26][27][28]. In previous works, the Department of Plastic and Hand Surgery, Medical Center-University of Freiburg, Faculty of Medicine, Freiburg, Germany, has shown that liquid biopsy can be used to monitor tumor dynamics, predict minimal residual disease and detect genetic tumor heterogeneities [3,[28][29][30][31][32][33][34]. The question remains, whether ctDNA can also be used as a biomarker for tumor activity.…”
Section: Introductionmentioning
confidence: 99%